2007
DOI: 10.1248/bpb.30.763
|View full text |Cite
|
Sign up to set email alerts
|

DNA Microarray Analysis of Type 2 Diabetes-Related Genes Co-regulated between White Blood Cells and Livers of Diabetic Otsuka Long-Evans Tokushima Fatty (OLETF) Rats

Abstract: In a previous study, we hypothesized that some type 2 diabetes mellitus susceptible genes may be up/downregulated in white blood cells (WBC) of Otsuka Long-Evans Tokushima Fatty (OLETF) rats, reflecting their up/down-regulation in major insulin-target tissues such as the liver before the onset of diabetes. We identified 57 potential candidate genes for predicting diabetes. In this study, we examined this hypothesis further by extending the experimental conditions from before the onset (6 weeks) to after the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…5A). These data are consistent with previous findings indicating that phosphorylation of Akt increases during adipocyte differentiation (20) and that BSTA amounts are increased in human skeletal muscle by insulin treatment (29) and are higher basally in adipose and liver tissue in ob/ob obese mice (30). To determine whether BSTA had a function in adipogenesis, we knocked it down in 3T3 L1 preadipocytes before inducing differentiation.…”
Section: Resultssupporting
confidence: 93%
“…5A). These data are consistent with previous findings indicating that phosphorylation of Akt increases during adipocyte differentiation (20) and that BSTA amounts are increased in human skeletal muscle by insulin treatment (29) and are higher basally in adipose and liver tissue in ob/ob obese mice (30). To determine whether BSTA had a function in adipogenesis, we knocked it down in 3T3 L1 preadipocytes before inducing differentiation.…”
Section: Resultssupporting
confidence: 93%
“…Blood, which is the most readily accessible cellular material in human intervention studies, interacts with every organ and tissue in the body and has crucial roles in immunity and inflammation. It has been reported that the expression of some genes in the peripheral white blood cells (WBC) reflects their expression in the liver, one of the major insulin target tissues, although blood is not a major insulin target tissue [9,10]. Some studies have shown that gene expression in the WBC may reflect nutrition-related metabolic changes such as fasting and differences in the macronutrient content or the fatty acid composition [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…7,[11][12][13] It would be interesting to examine whether change in expression is a cause or result of (pre-) diabetic state, for each gene. Detailed analyses of these genes, as well as the Asns gene, would help us understand the molecular mechanisms associated with the onset of T2DM, develop diagnostic tools for T2DM before onset, and establish fundamental therapies for the disease.…”
Section: Resultsmentioning
confidence: 99%